Genetic Mapping in Papillon-Lefèvre Syndrome: A Report of Two Cases - Kaustubh Suresh Thakare; M. L. Bhongade; Pretti Charde; Shweta Kale; Priyanka Jaiswal; B. K. Somnath; Sunil Pendor (Hindawi Limited, 2013)
Papillon-Lefevre syndrome (PLS) is a rare autosomal recessive heterogeneous trait which is characterized by erythematous palmoplantar hyperkeratosis, early-onset periodontitis, and associated calcification of dura mater. The etiology of PLS is multifactorial with genetic, immunological, and microbial factors playing a role in etiopathogenesis. Recently identified genetic defect in PLS has been mapped to chromosome 11q14-q21, which involves mutations of cathepsin C. This paper presents a report of 2 cases of Papillon-lefevre syndrome in which diagnosis is based on clinical presentation and genetic mapping.